Characterization of Diarrheagenic Enteroaggregative Escherichia coli in Danish Adults—Antibiotic Treatment Does Not Reduce Duration of Diarrhea - Betina Hebbelstrup Jensen; Betina Hebbelstrup Jensen; Camilla Adler Sørensen; Stig Hebbelstrup Rye Rasmussen; Dorthe Rejkjær Holm; Alice Friis-Møller; Jørgen Engberg; Hengameh C. Mirsepasi-Lauridsen; Carsten Struve; Anette M. Hammerum; Lone Jannok Porsbo; Randi Føns Petersen; et al. (Frontiers in Cellular and Infection Microbiology, 2018)
Enteroaggregative Escherichia coli (EAEC) is frequently isolated from sporadic cases of diarrhea and in outbreaks of gastroenteritis in several regions of the world. The pathophysiology of EAEC continues to be enigmatic, and the efficacy of antibiotic treatment in EAEC-associated diarrhea has been discussed. Since the level of antibiotic resistance is increasing, it is essential to restrict the use of antibiotics to prevent further resistance development. We aimed to investigate EAEC strains in adult Danish patients suffering from diarrhea and from healthy controls. We examined the antibiotic resistance in EAEC strains, the clinical response to antibiotic treatment in EAEC diarrheal cases, and the distribution of virulence genes in diarrheal cases. The EAEC strains were collected from patients suffering from diarrhea in a Danish multicenter study. A medical doctor interviewed the patients by using a questionnaire regarding gastrointestinal symptoms, exposures, and use of antibiotic and over-the-counter antidiarrheal drugs. Follow-up was performed after 3–5 months to inquire about differential diagnosis to gastrointestinal disease. A multiplex polymerase chain reaction characterized virulence genes in diarrheal cases. Finally, the level of antibiotic resistance was examined by using the disc diffusion method. Asymptomatic carriage of EAEC in the adult Danish population was rare, in contrast to findings in healthy Danish children. The duration of diarrhea was not shortened by antibiotic treatment, specifically ciprofloxacin treatment, or by over-the-counter antidiarrheal drugs. Follow-up revealed no pathology in diarrheal patients apart from irritable bowel syndrome in two patients. A high number of patients suffered from long-term diarrhea, which was associated with the enterotoxin EAST-1 and a high virulence factor score. A high level of antibiotic resistance was observed and 58% of the EAEC strains were multidrug resistant. Multidrug resistance was most pronounced in cases of travelers' diarrhea, and it was seen that antibiotic treatment did not reduce the duration of diarrhea.